Antioxidant capacity of fermented corn gluten meal in broiler chickens: a solid-state approach with mixed microbial fermentation - Yu Zhao; Yongping Deng; Tong Guo; Hao Wu; Tingpeng Lv; Xiaolan Liu (Poultry Science)
ABSTRACT: Fermentation of feed with probiotic and biofunctional properties has gained global attention for its potential to enhance digestive absorption and improve overall functional quality. This study investigates the antioxidant capacity and expression of antioxidant-related genes in broiler chickens fed with fermented corn gluten meal (FCGM) containing mixed microbial cultures. Seventy-two male Yellow-Feathered broiler chickens were randomly assigned to 2 groups, each consisting of 3 replicates, and were fed experimental diets containing either corn gluten meal or FCGM for 42 d. The antioxidant capacity of FCGM was assessed in vivo. Chickens fed with FCGM exhibited significant increases in serum glutathione concentration, as well as enhanced activities of total superoxide dismutase, glutathione peroxidase, and catalase (CAT) in their serum. Similar trends were observed in the liver, specifically in the activities of glutathione peroxidase and CAT. Additionally, the expression levels of key antioxidant-related genes in the liver, such as glutathione synthase, superoxide dismutase 1, superoxide dismutase 2, CAT, and glutathione peroxidase 1, were examined. The results indicated that FCGM significantly enhanced antioxidant capacity in broiler chickens. This study highlights the potential benefits of utilizing solid-state fermentation with mixed microbial cultures to improve the antioxidant properties of corn gluten meal, thereby contributing to the overall health and well-being of broiler chickens.